Income inequality, globalization, and country risk: a cross-country analysis - Lee, Chi-Chuan; Lee, Chien-Chiang; Lien, Donald (Technological and Economic Development of Economy, 2020)
Guided by the assessments of globalization in its broader sense, this paper explores the impact of globalization in terms of a salient aspect of economic, social and political on income inequality for a more comprehensive dataset of 121 countries from 1984 to 2014. We also investigate whether the correlations between globalization and inequality vary with economic, financial, and political country risk indicators. Our empirical results reveal that globalization deteriorates income distribution, but economic and financial stability can mitigate the adverse effect. In addition, lowerincome or non-OECD countries generally have higher inequality caused by globalization. Knowledge of these relationships can help the government to formulate more specific policies aiming at improving the income distribution. First published online 13 December 2019